Identification and characterization of endogenous retroviruses upon SARS-CoV-2 infection - Guo, Xuefei; Zhao, Yang; You, Fuping (Frontiers in Immunology, 2024)
Endogenous retroviruses (ERVs) originating from the long terminal repeat (LTR) family of transposons constitute a significant portion of the mammalian genome. These genetic elements trace their origins to ancient viruses that once infected mammalian hosts and now comprise about 8% of the human genome. ERVs are pivotal in various biological processes, including viral infection pathogenesis, immune response activation, and tumorigenesis. However, the specific function of ERVs during the pathogenesis of COVID-19 remains unclear. In this study, we conducted a genome-wide identification of ERVs in human peripheral blood mononuclear cells (hPBMCs) and primary lung epithelial cells from monkeys and mice, both infected and uninfected with SARS-CoV-2. We identified 405, 283, and 206 significantly up-regulated transposable elements (TEs) in hPBMCs, monkeys, and mice, respectively. This included 254, 119, 68, and 28 ERVs found in hPBMCs from severe and mild COVID-19 patients, monkeys, and transgenic mice expressing the human ACE2 receptor (hACE2) and infected with SARS-CoV-2. Furthermore, our analysis using the Genomic Regions Enrichment of Annotations Tool (GREAT) revealed that certain parental genomic sequences of these up-regulated ERVs in COVID-19 patients may be involved in negative regulation of histone H3-K36 methylation, histone H3-K4 methylation, Gprotein coupled receptor signaling pathway, histone H2A ubiquitination, ER ubiquitin ligase complex, as well as components of the virion part, viral replication complex, and respiratory chain complex IV. Of particular interest, we identified 210 ERVs that were specifically up-regulated in the severe COVID-19 group. The genes associated with these differentially expressed ERVs were enriched in processes such as Toll-like receptor 2 binding, T cell activation, and histone H3-K4 demethylation. Notably, HERV1_I-int: ERV1:LTR and LTR7Y: ERV1:LTR were highlighted as potential biomarkers for evaluating the severity of COVID-19. Moreover, we validated our findings using RT-qPCR to examine some up-regulated ERVs in Bone Marrow-Derived Macrophages (BMDMs) from mice infected by HSV-1 and VSV. These results offered insights into the expression patterns and potential roles of ERVs following viral infection, providing a valuable resource for future studies on ERVs and their interaction with SARS-CoV-2.